(untitled) - Saga, Junichi (New York, 1987)
Contents: Preface Introduction, Around the town, Boatmen and fishermen, Shopkeepers and tradesmen, Women of the town, Geisha and Officers, Life in the countryside, Crafts and craftsmen, At school and at play.
Keywords: Nhật Bản,Japan; Đời sống và phong tục xã hội,Social life and customs; 1912-1945,1912-1945